A year of clouds storm and cloud tropes between the Manila observatory and the Katipunan, 1896-1897 - Lacuna, Isa (2023)
While the discourse surrounding the 1896 Philippine Revolution is often read to support political interpretations of Philippine history, less studied are the ways weather tropes shape this discourse. Meteorology's scientific empiricism was introduced to a general atmospheric rhetoric tending toward allegorical and romantic figurations, creating a palpable shift in signifying maneuvers, both political and literary. The convergence and divergence of these different storm-knowledges in the popular folk imagination of the Philippines map the ways these varying elements were tactically assembled, and give an account of how folk writers actively engaged and became entangled with their environmental and political worlds.
Keywords: Philippines -- History -- Revolution, 1896-1898; Ecocriticism; Katipunan